Modelling the influence of teachers’ knowledge and student-teacher relationship on students’ perceived achievement in trigonometry - Boniface Aabeyir; Francis Boateng; Ebenezer Bonyah; John Amoah-Mensah (Universitas Sarjanawiyata Tamansiswa, 2025)
This paper investigated the effects of teachers’ subject matter knowledge, pedagogical content knowledge and student-teacher relationship on students’ perceived achievement in trigonometry. The paper also investigated the indirect effect of pedagogical content knowledge on students’ perceived mathematics achievement through subject matter knowledge. A six-point Likert scale questionnaire was used to collect data on teachers’ subject matter knowledge, pedagogical content knowledge, student-teacher relationship and students’ perceived achievement in trigonometry. Stratified sampling technique was used to select five schools in the Bekwai Municipality, comprising three public schools and two private schools. In all, 460 students were sampled. Partial least squares structural equation modelling was used to develop a model indicating the direct relationships between student-teacher relationship, teachers’ subject matter knowledge, pedagogical content knowledge and students’ perceived achievement in trigonometry. The results indicated that student-teacher relationship had no significant influence on students’ perceived achievement in trigonometry. However, both subject matter knowledge and pedagogical content knowledge significantly and positively influence students’ perceived achievement in trigonometry. It was also established that pedagogical content knowledge partially mediated the relationship between teachers’ subject matter knowledge and students’ perceived mathematics achievement. The study concludes that teachers’ subject matter knowledge and pedagogical content knowledge significantly enhance students’ perceived achievement in trigonometry, while student-teacher relationship shows no significant impact. The study shows that teacher content and pedagogical knowledge significantly impact students’ perceived trigonometry achievement, highlighting key areas for teacher development. It is recommended that stakeholders in education such as Ministry of Education, Ghana Education Service, teacher unions and heads of secondary schools should frequently organize workshops/seminars for mathematics teachers to improve upon their mastery of the subject matter knowledge including trigonometry. Seminars on mathematics teachers’ professional development should be tailored toward equipping teachers with the requisite pedagogical skills in trigonometry.